Cell-Free Synthesis of Factor VIII Related Protein - Chan, Vivian; Chan, T K (Thrombosis and Haemostasis, 1983)
Polyadenylated ribonucleic acid (RNA) was isolated from confluent human endothelial cells in culture and translated in a cell-free rabbit reticulocyte lysate protein-synthesizing system. Using specific immunopredpitation, the translation product was found to contain 1.58% VIH related protein (VIIIR), which has a molecular weight of 0.26 × 106, similar to the subunit of VIIIR present in normal plasma. This indicated that VIIIR messenger RNA is responsible for the synthesis of subunits only and intracellular post-translational events are required for the assembly of tetramer and multimers.
Keywords: Factor VIII related protein; Cell-free synthesis; Human endothelial cells; Messenger RNA